In search of a causal relationship between industrial output and employment in Ireland: a comment - Thom, Rodney; Fell, John P.C. (Economic & Social Studies, 1989)
John Fell has produced a stimulating paper which uses V A R methodology to address the issue of causal relationships between employment and output at both aggregate and disaggregated levels. Given the techniques employed, it is difficult to comment on the results. My personal view is that aresult such as output does not "Granger cause" employment is a characteristic of the data set and should not be used as a definitive guide to choosing between competing theories. Nevertheless, when such results can be shown to be robust to alternative data sets then they cannot be ignored in formal model building. Hence Fell's conclusion that causality is absent in both aggregate and industry data must have implications for our thinking about these relationships and about policies designed to stimulate employment. Further, his finding that the relationship between real wages and output is stronger in modern industries has similar implications and provides a useful pointer to future research. This paper casts a disturbing light on, for example, Barry (1989).
Keywords: Industrial output; Employment; manufacturing sector; Ireland